Structural and optical properties of Zn0.9 Mn0.1 O/ZnO core-shell nanowires designed by pulsed laser deposition - Kaydashev, V.E. (2012)
Core-shell ZnO/ZnMnO nanowires on a-Al2O3 and GaN (buffer layer)/Si (111) substrates were fabricated by pulsed laser deposition using a Au catalyst. Two ZnO targets with a Mn content of 10% were sintered at 1150 and 550 °C in order to achieve the domination in them of paramagnetic MnO2 and ferromagnetic Mn2O3 phases, respectively. Cluster mechanism of laser ablation as a source of possible incorporation of secondary phases to the wire shell is discussed. Raman spectroscopy under excitation by an Ar+ laser revealed a broad peak related to the Mn-induced disorder and a redshift in the A1-LO phonon. Resonant Raman measurements revealed an increase in the multiphonon scattering caused by disorder in ZnO upon doping by Mn. Besides the UV emission, a vibronic green emission band assisted by a ∼ 71 meV LO phonon is also observed in the photoluminescence spectra. Core-shell structures with smooth shells show a high exciton to green band intensity ratio ( ∼ 10) even at room temperature. © 2009 American Institute of Physics